The impact of air transportation, trade openness, and economic growth on CO2 emissions in Saudi Arabia - Aldegheishem, Abdulaziz (Frontiers in Environmental Science, 2024)
The global economy has reported an unprecedented increase in growth rates over the last 2 decades, due to rapid evolution in transportation and communications. The rapid growth of international trade has increased the demand for fossil fuel, leading to exacerbated environmental risks. Air transportation is an essential operational practice in trade openness and has many economic benefits. However, its effect on CO2 emissions is not well understood. Studies on the causal relationships between air transportation, trade openness, economic growth, and CO2 emissions are lacking, especially across Middle Eastern countries. This study targets Saudi Arabia, one of the largest countries in the Middle East region in terms of economic capabilities and geographical area, to investigate the impact of air transportation, trade openness, and economic growth on CO2 emissions. To this end, data was derived from the World Development Indicators (WDI) established by the World Bank for the period 1991–2023. An autoregressive, distributed lag autoregressive distributed lag (ARDL) model was used to analyze associations among the study variables; the empirical findings confirm that air transportation, trade openness, and economic growth have positive and statistically significant effects on CO2 emissions in both long- and short-run scenarios. However, the results illustrate that economic growth alone is unable to sufficiently reduce CO2 emissions in Saudi Arabia, indicating a lack of connection between economic policies and environmental goals. Thus, these results indicate that the Environmental Kuznets Curve (EKC) hypothesis is not valid for Saudi Arabia. In addition, this study provides useful insights for policymakers to mitigate CO2 emissions. Suggestions include attracting foreign investment, modifying the structure of trade, mitigating the reliance on imports and enhancing exports, while focusing on green strategies for economic growth, replacing fossil fuels with clean and renewable sources, subsidizing environmentally friendly technologies, and enacting decarbonizing regulations.